The Effect of Rotational Speed, Friction Duration, and Pressure on Tensile Strength of AISI 6061 Welding Joints - Dewi Puspitasari; Poppy Puspitasari; M. Rizka Gita Firmansyah; Solichin Solichin (Universitas Negeri Malang, 2018)
Electric arc welding with covered electrodes is ideally suited for flat plates. If this technique is employed for welding rigid bodies, the results would be of poor quality. One viable solution to weld rigid bodies is through friction welding. The study aimed to investigate the tensile strength of specimens subjected to friction welding with variations in rotational speed, friction time, and pressure and to examine the microstructure of friction welding joints. This research used the one-shot case study design and involved descriptive analysis. The descriptive analysis described the results of tensile testing and microstructure of welding joints. Results showed that the specimen subjected to a 2850 rpm rotational speed, 60-second friction duration, and 8 MPa pressure had the highest tensile strength of 15.19 Kgf, whereas that rotated at 2850 rpm under 8 MPa pressure for 80 seconds had the lowest tensile strength, i.e. 12.25 Kgf. The photomicrographs showed that the friction welding joints underwent no phase change, but the refinement of Mg2Si particles occurred in the Zpd and Zpl zones. Also, the Zud zone consisted of the same form of Mg2Si particles as the untreated specimen.